Ability Emotional Intelligence and Subjective Happiness in Adolescents: The Role of Positive and Negative Affect. - Llamas-Díaz, Desirée; Cabello-González, Rosario; Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Megías-Robles, Alberto; Fernández-Berrocal, Pablo (MDPI, 2023)
Adolescence is an increasingly vulnerable period for the onset of affective disorders and other mental health issues that can significantly impact an individual’s subjective well-being. This study aims to examine the relationship between emotional intelligence (ability EI), measured with a performance-based instrument, and Subjective Happiness in adolescents. It also explores the mediating role of positive (PA) and negative affect (NA) in this association and the moderating role of gender. The sample consisted of 333 first-year secondary school students from five centers in Spain, with an average age of 12.11 years (SD = 0.64), ranging from 11–14 years. Path analysis revealed an indirect effect (through NA and PA jointly) of Total Ability EI on Subjective Happiness and a positive direct effect that was observed only in females. Furthermore, this association was explored through various branches of ability EI. The results of this study suggest that interventions aimed at improving emotional abilities in adolescents while modulating the intensity of their emotions could significantly impact their overall well-being.
Keywords: Emociones; Adolescentes - Psicología; Madurez afectiva; Emotional intelligence; Positive affect; Negative affect; Subjective happiness; TIEFBA; PANAS; Adolescence; Ability EI; Gender